THE DIFFERENCE OF ANATOMICAL INFORMATION AND IMAGE QUALITY OF NASOPHARYNX CARCINOMA CT SCAN WITH SLICE THICKNESS VARIATION ON AXIAL SLICE IN RSUD DR MOEWARDI SURAKARTA - Aisyah Amalia Dewita Rachmani; Siti Masrochah; Sri Mulyati (Jurnal Imejing Diagnostik (JImeD), 2018)
Background : The use of Slice thickness examination of nasopharyngeal CT based on theory (Seeram, 2001) using 3 mm and according (Ballinger, 2010) using 5 mm, while in hospital Dr. Moewardi Surakarta the slice thickness used is 5 mm according to theory and 7 mm based on the radiographer. The purpose of this research is to know the difference of anatomical information and image quality of CT scan of nasopharynx of carcinoma case and to know the slice thickness that produces anatomical information and the best image quality CT Scan nasopharynx case carcinoma.Method : The type of research is a quantitative with experimental approach. The data were obtained from 10 nasopharynx CT patients with carcinoma using variations of slice thickness 3 mm, 5 mm, and 7 mm. The assesment of anatomical information and image quality by spreading questionnaire at 3 doctor radiolog. Data were tested with Shapiro Wilk for normality data, then friedman test. To determine the optimal slice thickness using descriptive mean rank test.Results : The results showed that there were differences in anatomical information and image quality of nasopharyngeal CT scan of axial slice using slice thickness. The probability value of this study is p value = 0,000 (0,05). Optimal slice thickness on nasopharyngeal CT scan for anatomical information using slice thickness of 5 mm with the highest mean rank of 2.61 and for viewing image quality it is best to use slice thickness of 7 mm with a mean rank of 3.00.Conclusion : There are differences in anatomical information and image quality on nasopharynx CT scans of carcinoma cases using slice thickness variations. The optimal slice thickness is 5 mm slice thickness to anatomical information and the optimal slice thickness is 7 mm  to quality image.